2005
DOI: 10.1111/j.0105-1873.2005.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre review of the hairdressing allergens tested in the UK

Abstract: Allergens used for patch testing in the hairdressing series vary between dermatology centres in the UK. The aim of our study is to ascertain the hairdressing allergens currently in use and their test results in several dermatology centres in the UK. Data were obtained from databases in 9 dermatology departments. The allergens with positive results and current/past relevance were included in a new hairdressing series based on collective experience, for wider use and further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Lund et al reported that hair highlighting products could be irritating and corrosive to skin and raised a concern that it might induce hair loss although neither exact causative ingredients nor mechanism underlying were provided. It was also reported that the increased use of oxidative hair dyes are often implicated in hair loss and chronic skin inflammation [4,6,28]. Despite the wide awareness of the risk of hair loss and dermatitis associated with hair dye products, few researches have been focused on the identification of the causative ingredients or the mechanism underlying it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lund et al reported that hair highlighting products could be irritating and corrosive to skin and raised a concern that it might induce hair loss although neither exact causative ingredients nor mechanism underlying were provided. It was also reported that the increased use of oxidative hair dyes are often implicated in hair loss and chronic skin inflammation [4,6,28]. Despite the wide awareness of the risk of hair loss and dermatitis associated with hair dye products, few researches have been focused on the identification of the causative ingredients or the mechanism underlying it.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the increased use of hair dye product, complaints are growing about the sideeffects of hair dye on the scalp and hair, itself. There are reports that hair dye products can cause skin inflammation in ears, neck and shoulders [3][4][5][6]. Also notable are the frequent complaints on the hair dye-induced hair loss [7] and the concern over carcinogenicity associated with percutaneous absorption of toxic ingredients [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…PPD sensitization manifests on the face and scalp of female adult patients who had contact with a hair dye. [32][33][34][35] In a small Brazilian study, Duarte and colleagues 32 identified that in patients with positive patch test reactions to PPD (mostly females between 41 and 60 years of age), 70% had face or scalp involvement, and 48% had hair dye as the agent responsible for the sensitization.…”
Section: Facial Dermatitismentioning
confidence: 99%
“…Our current hairdressing series does not include TBHQ; however, a recent review of allergens in the hairdressing series in the UK has suggested its inclusion (8). The authors also recommended testing both the hairdressing series and the facial series in all patients with possible ACD to hair care products.…”
Section: Discussionmentioning
confidence: 99%